Inactivation of Listeria monocytogenes and Salmonella Typhimurium in strawberry juice enriched with strawberry polyphenols - Vallejo, Claudia Veronica (2021)
BACKGROUND: Low molecular-weight phenolic fractions (LMPFs) were extracted from Albion (LMPF-A) and Camarosa (LMPF-C) strawberry cultivars. Their antibacterial activity against Listeria monocytogenes and Salmonella Typhimurium cocktails in vitro and in vivo was investigated using strawberry juice as a food model. This study also sought to determine their antibacterial mechanism. RESULTS: Quercetin was identified as a principal compound in both phenolic fractions. The minimum bactericide concentration (MBC) values were 750 and 850 μg mL−1 (LMPF-C) and 800 and 950 μg mL−1 (LMPF-A) against S.Typhimurium and L. monocytogenes, respectively. The possible antibacterial activity of the phenolic extracts could be related to the release of phosphate and potassium ions, the effect of the disruption of membrane integrity on L. monocytogenes, and the effect of the inhibition of dihydronicotinamide adenine dinucleotide (NADH) oxidase activity on S. Typhimurium. Quercetin and kaempferol were the most active compounds in producing bacterial damage. Strawberry juice supplemented with the phenolic fractions and incubated at 37, 20, and 4 °C reduced bacterial viability; moreover, after treatment with the phenolic fraction at the lowest temperature, no viable cells were detected after 7 days’ incubation. Salmonella was more sensitive to the supplements than Listeria in strawberry juice. CONCLUSIONS: This study could form the basis for the development of natural antibacterial agents that could be included in natural juice or used by the pharmaceutical industry.